2016
DOI: 10.1183/13993003.01384-2015
|View full text |Cite
|
Sign up to set email alerts
|

Serum periostin in obstructive airways disease

Abstract: Serum periostin is a potential biomarker of response to therapies that target type 2 inflammation in asthma. The objectives of this study were to describe: 1) the distribution of serum periostin levels in adults with symptomatic airflow obstruction; 2) its relationship with other variables, including type 2 biomarkers; and 3) the effect of inhaled corticosteroids on periostin levels.Serum periostin levels were measured in a cross-sectional study exploring phenotypes and biomarkers in 386 patients aged 18–75 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
35
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 32 publications
10
35
0
4
Order By: Relevance
“…These values are also similar to the median level of 50.2 ng/mL previously reported in adults with moderate and severe asthma inadequately controlled despite ICS therapy , and the median levels ranging from 46.4 to 49.5 ng/mL at baseline in adults with uncontrolled asthma despite high‐dose ICS therapy and a second controller, randomized to the four treatment groups . Likewise, the mean serum periostin level of 51.2 ng/mL was similar to the mean value of 53 ng/mL reported in severe persistent allergic asthma uncontrolled despite treatment with high‐dose ICS plus long‐acting beta‐agonist therapy and 57.7 ng/mL reported in our random adult population with asthma These findings suggest that periostin is not a measure which can usefully diagnose patients with asthma or discriminate patients with asthma receiving different treatment regimens across a range of severity, or from a population without asthma or COPD. It also suggests that asthma is not the major determinant of serum periostin levels and that pathophysiological processes related to its function as a matricellular protein, with expression typically confined to cells of mesenchymal origin, are likely to play a greater role .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These values are also similar to the median level of 50.2 ng/mL previously reported in adults with moderate and severe asthma inadequately controlled despite ICS therapy , and the median levels ranging from 46.4 to 49.5 ng/mL at baseline in adults with uncontrolled asthma despite high‐dose ICS therapy and a second controller, randomized to the four treatment groups . Likewise, the mean serum periostin level of 51.2 ng/mL was similar to the mean value of 53 ng/mL reported in severe persistent allergic asthma uncontrolled despite treatment with high‐dose ICS plus long‐acting beta‐agonist therapy and 57.7 ng/mL reported in our random adult population with asthma These findings suggest that periostin is not a measure which can usefully diagnose patients with asthma or discriminate patients with asthma receiving different treatment regimens across a range of severity, or from a population without asthma or COPD. It also suggests that asthma is not the major determinant of serum periostin levels and that pathophysiological processes related to its function as a matricellular protein, with expression typically confined to cells of mesenchymal origin, are likely to play a greater role .…”
Section: Discussionsupporting
confidence: 87%
“…We observed that the distribution of serum periostin levels in this population without asthma or COPD was relatively wide, with a fivefold range of levels (28.1–136.4 ng/mL), and a marked right skew distribution. The median serum periostin level of 50.1 ng/mL was similar to the median level of 53.7 ng/mL we reported in a random adult population with a doctor's diagnosis of asthma, using the same laboratory and assay to measure periostin levels . These values are also similar to the median level of 50.2 ng/mL previously reported in adults with moderate and severe asthma inadequately controlled despite ICS therapy , and the median levels ranging from 46.4 to 49.5 ng/mL at baseline in adults with uncontrolled asthma despite high‐dose ICS therapy and a second controller, randomized to the four treatment groups .…”
Section: Discussionsupporting
confidence: 85%
“…Nevertheless, the majority of published reports in adults do demonstrate modest, yet significant relationships between circulating periostin with other proposed markers of type 2 inflammation, including exhaled NO, sputum, and blood eosinophils or total IgE [5355]. …”
Section: Bloodmentioning
confidence: 99%
“…Nitric oxide is produced by the action of iNOS encoded by the NOS2 gene, and eosinophils are mobilized by chemokines such as eotaxin-3 encoded by the CCL26 gene, both of which are inducible by IL-13 and highly correlated with the Th2 signature (18). The half life of blood eosinophils in humans is several days (19) and it is likely that serum periostin levels may fluctuate on a similar time scale (20), while serial bronchoscopy studies with anti-IL5 suggest that bronchial tissue, but not sputum eosinophils, may persist for weeks to months (21). Thus, FeNO and sputum eosinophils may reflect acute activity of type 2 cytokines in the airways whereas tissue eosinophils and blood biomarkers may reflect aggregate type 2 airway inflammation over longer time intervals.…”
mentioning
confidence: 99%